Classification of Exact Solutions for Some Nonlinear Partial Differential Equations with Generalized Evolution - Yusuf Pandir; Yusuf Gurefe; Ugur Kadak; Emine Misirli (Abstract and Applied Analysis)
We obtain the classification of exact solutions, including soliton, rational, and elliptic solutions, to the one-dimensional general improved Camassa Holm KP equation and KdV equation by the complete discrimination system for polynomial method. In discussion, we propose a more general trial equation method for nonlinear partial differential equations with generalized evolution.